« Etat composé » ou décomposé ? - Nacima Baron (L'Espace Politique)
The Spanish Constitution of 1978 shares the power between the State and the Autonomous Communities. Over the past three decades, the principle of this "compound state" has become reality. A large amount of social, economical or environmental responsabilities have been transfered to the autonomous communities, which have built strong peripherical powerships. In this general frame, the article analyses the last period (2004-2010) of the commmunitie’s political emancipation and hightlights president Zapatero’s strategy at two different (and interconnected) levels : from one part, the renewal of the « statutos » (the fundamental law governing autonomous communities) ; from the other part, the choice of criterias ruling the distribution of regional financement. This long and conflictual process gives the opportunity to reconsider the question of the spanish institutional and territorial organization through the concept of fragmentation.